2013
DOI: 10.4037/ajcc2013659
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis Masquerading as Catastrophic Antiphospholipid Syndrome

Abstract: A 25-year-old woman with a history of systemic lupus erythematosus who was taking steroids came to the hospital because of vague signs and symptoms of weight loss, constipation, and oral ulcers. Multiorgan dysfunction developed, and catastrophic antiphospholipid syndrome was suspected. She was treated with an intravenous infusion of heparin, but she experienced a subdural hemorrhage and died on day 10 of the hospitalization. An autopsy revealed disseminated invasive aspergillosis. This case illustrates that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Fifth, routine autopsy would have increased the number of cases of IA diagnosis. Autopsy studies have shown that IA is the most frequently missed infection diagnosis in patients requiring ICU admission [ 15 , 49 , 50 ]. Sixth, we did not consider environmental sources of IA, such as construction work contaminating hospital air [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, routine autopsy would have increased the number of cases of IA diagnosis. Autopsy studies have shown that IA is the most frequently missed infection diagnosis in patients requiring ICU admission [ 15 , 49 , 50 ]. Sixth, we did not consider environmental sources of IA, such as construction work contaminating hospital air [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is difficult because 30% to 50% patients show no evidence of the fungus in blood and sputum cultures. Test for galactomannan, a polysaccharide of the Aspergillus cell wall, which can be performed on various biologic specimens, is a useful diagnostic tool [ 58 , 59 ]. Pneumocystis jiroveci pneumonia (PJP) is a fungal opportunistic infection unfrequently observed in profound immunosuppressed SLE patients.…”
Section: Lung Infections In Systemic Rheumatic Diseasesmentioning
confidence: 99%
“…Invasive aspergillosis (IA) is the most severe infection caused by A. fumigatus and occurs when fungal growth, most commonly originating in the lung, disseminates to other parts of the body via the bloodstream (Latge, 1999 ). A. fumigatus is an opportunistic pathogen primarily affecting immunocompromised individuals, and unfortunately, infections have become more common due to the increased usage of immunosuppressive drugs to treat autoimmune disorders and to increase the success of organ transplantation surgery (Robinett et al, 2013 ; Neofytos et al, 2018 ; Latge and Chamilos, 2019 ). Even when aggressively treated with first and second-line antifungal medication, mortality rates can exceed 50% in IA patients (Latge, 1999 ; Lin et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%